Social Networks in the Strategies of Job Seeking in Russian Labour Market - ЛаврусевичПолина Евгеньевна (Journal of Economic Sociology, 2010)
The aim of the study is to analyse the strategies of job seeking in Russian labour market in the context of using social networks as a way of job seeking that is to consider how the strategies of job seeking are constructed around the social networks. The 9-13th waves of RLMS (1998-2004) are used as a database.